Peran Zakat dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat: Studi Kasus: Lazismu Kota Metro - Aurelia Cahya Aini; Dea Marsa Amelia; Devika Putriani; Farhan Trisna Maulana; Akhmad Kholil; Siti Zulaikha (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study investigates the role of zakat, particularly productive zakat, in improving the economic welfare of the community in Metro City, focusing on LAZISMU Metro City. Zakat is not merely an individual obligation but a strategic instrument for social justice and economic balance, aiming to empower recipients to become self-sufficient. The research employed a qualitative descriptive field study approach, utilizing literature review, interviews, and documentation for data collection. Findings indicate that LAZISMU Metro City's productive zakat programs, such as business capital assistance (e.g., for mini molen vendors), rolling goat programs, and waste management initiatives, have positively impacted mustahik welfare by fostering economic independence and enhancing their income. While some challenges like the misuse of aid were noted, responsive evaluations and adaptive assistance forms ensured the program's overall effectiveness in transforming mustahik into muzakki.